Theo-genetiese kodes van die APEHL, soos afgelei uit Efesiërs 4, beliggaam - Merwe, J. Christo van der (HTS teologiese studies, 2017)
The focus of this article is on the incarnation of Jesus Christ, the Word become flesh, as a way of talking about and understanding mission and addresses at least two concerns in the contemporary debate about the missional church. Many missionary methods and strategies have contradicted both the teaching and actions of Jesus as he trained his disciples to continue his ministry. The message may have been the gospel, but the way the message was made known was often not congruent with the gospel. The attempt to interpret mission in terms of the incarnation of Jesus suggests that the earlier forms of mission strategies should be replaced by a theology and praxis rooted in and defined by the life and ministry of Jesus. Ephesians 4 provides the key to the theology and praxis by giving us a direct link backward into the ministry that infused and led the early church in the life and the ministry of Jesus.